Under attack: Terrorism and international trade in France, 2014-16 - Volker Nitsch; Isabelle Rabaud (Technische Universität Darmstadt, Department of Law and Economics, 2021)
Terrorist events typically vary along many dimensions, making it difficult to identify their economic effects. This paper analyzes the impact of terrorism on international trade by examining a series of three large-scale terrorist incidents in France over the period from January 2015 to July 2016. Using firm-level data at monthly frequency, we document an immediate and lasting decline in cross-border trade after a mass terrorist attack. According to our estimates, France's trade in goods, which accounts for about 70 percent of the country's trade in goods and services, is reduced by more than 6 billion euros in the first six months after an attack. The reduction in trade mainly takes place along the intensive margin, with particularly strong effects for partner countries with low border barriers to France, for firms with less frequent trade activities and for homogeneous products. A possible explanation for these patterns is an increase in trade costs due to stricter security measures.
urn:nbn:de:tuda-tuprints-186090
Keywords: F14; F52; 330; shock; insecurity; uncertainty; terrorism; international trade; France